Developing an Ethic of Justice: Maqāṣid Approaches in Maududi and Solidarity Youth Movement (American Journal of Islam and Society, 2022)
New Muslim movements in South India, such as the Solidarity Youth movement, re-formulated Muslim priorities towards human rights, democracy, development, environmental activism, and minorities. I read Solidarity Youth Movement as proposing an ethic of  Islam’s conception of justice, while also drawing inspiration from the influential Islamist Abul A’la Maududi. Focusing on  jurisprudential debates, I look at the ways in which Maududi’s intervention informs the praxis of Solidarity Youth Movement. This  paper seeks the possibility of examining their activism as an instance of juristic deliberation, linked to the revival of maqāṣid al-sharī’ah in the latter part of the twentieth century. I suggest a reading of their maqāṣid approach, born out of praxis in a Muslim minority  context, as potentially informing the development of fiqh al-aqalliyah.